(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
African philosophy deserves special attention and increased efforts in exploring its components and shaping frameworks in contemporary thought. The history of thought in Africa, especially in the Black Continent, requires the awareness and commitment of humanity to embody a distinctive philosophical character that outlines new dimensions in the realm of global thought and culture. Such a comprehensive understanding of African philosophy in the context of historical development is essential. Moreover, this historical development requires attention to the fact that it is not merely a search for truth, but should serve as its core nucleus.